The associations between domain-specific sedentary behaviours and dietary habits in European adults: a cross-sectional analysis of the SPOTLIGHT survey. (December 2016) - Compernolle, Sofie; De Cocker, Katrien; Teixeira, Pedro; Oppert, Jean-Michel; Roda, Célina; Mackenbach, Joreintje; Lakerveld, Jeroen; McKee, Martin; Glonti, Ketevan; Rutter, Harry; Bardos, Helga; Cardon, Greet; et al.
Abstract Background Sedentary behaviour has been associated with obesity and related chronic diseases. Disentangling the nature of this association is complicated due to interactions with other lifestyle factors, such as dietary habits, yet limited research has investigated the relation between domain-specific sedentary behaviours and dietary habits in adults. The aim of this paper was to examine the association between domain-specific sedentary behaviours and dietary habits in adults and to test the moderating effect of age and gender on this association. Methods A total of 6, 037 participants from five urban regions in Europe completed an online survey, of which 6, 001 were included in the analyses. Multilevel mixed-effects logistic regression analyses were used to examine main associations and interaction effects. Results All domain-specific sedentary behaviours, except transport-related sitting time, were significantly related to dietary habits. In general, having a higher sitting time was related to having less healthy dietary habits, especially for television viewing. Gender did not moderate any of the relations, and age was only a significant moderator in the relation between other leisure sitting time and alcohol consumption. Conclusion Domain-specific sitting behaviours were related to unhealthy dietary behaviours. However, the small effect sizes suggest that individual level behavioural interventions focusing on sedentary behaviour will not be sufficient to improve dietary habits. The fact that almost none of the associations were moderated by age or gender suggests that these associations, and possibly also the effects of interventions targeting both behaviours, may hold across age and gender groups.